Pembelajaran Struktur Aljabar Berbantu Design Batik Sasambo Untuk Menggali Potensi Kreatif dan Sikap Ilmiah Mahasiswa - Anwar, Yunita Septriana; Sirajudin, Sirajudin; Pramita, Dewi (Mandalika Mathematics and Educations Journal, 2025)
This study aims to measure students' creative thinking abilities based on the Torrance Tests of Creative Thinking (TTCT), which include fluency, flexibility, and novelty. It is a descriptive-qualitative study designed to describe and interpret tasks related to Group Theory in the Algebra Structure course. The learning process was conducted over three sessions, each involving structured discussions to assess students' abilities and creativity in learning Algebra Structure, supported by the Batik Sasambo design. The results show that applying the Batik Sasambo design in Algebra Structure learning can enhance students' creative thinking in understanding the concept of algebraic structures and solving simple algebra problems. In the first session, only some aspects of creativity were evident. For example, the observed components were fluency and flexibility. However, by the final session, all three aspects of creativity appeared simultaneously.